Annotated Chronological Bibliography (ACB) of Publications and Manuscripts in Philippine Linguistics Made by the Japanese - Shinoda, Eri B. (The Archive; Vol 6 (1990): Publication Six: Annotated Chronological Bibliography (ACB) of Publications and Manuscripts in Philippine Linguistics Made by the Japanese, 2025)
This 215-entry Bibliography aims at efficiently serving as a research and orientation tool for those who wish to familiarize themselves with the literature on the Philippine linguistics and languages contributed by the Japanese (cf. 2.4. Nationalities of the writers), and succinctly providing them with a reference source which summarizes the accumulated body of information and lists the names of contributors, the titles of their works, and the directions and progress of their researches and analyses in this particular field, from 1902 until the end of September ‘89 (cf. 1.6. For the additional entries after October ‘89)… … The geographical boundaries of the present Bibliography coincide with the spatial limits of the Republic of the Philippines. The sole exception, however, is Yami – one of the six Batanic (or Bashiic, or Vasayic) languages spoken on the small island called Lanyu (or Orchid Island, or Botel Topago in pre-War days) lying between Taiwan and Luzon, which politically belongs, not to the Philippines, but to Taiwan (cf. TSUCHIDA et al. (1989) (008); MORIGUCHI (1989b) (212) ). Yami has about two thousand native speakers on the island.